Patients with Specific Gastrointestinal Motility Disorders are Commonly Diagnosed as Functional GI Disorders in the Early Stage by Community Physicians due to Lack of Awareness - Ghoshal, Uday C.; Bhut, Bhavesh; Misra, Asha (Turkish Journal of Gastroenterology, 2021)
Background: Data on specific gastrointestinal (GI) motility disorders, such as gastroparesis (GP), chronic intestinal pseudo-obstruction(CIPO), and colonic inertia (CI), as well as awareness among doctors about these disorders are scanty in Asia.Method: Prospectively maintained records of 60 patients were retrospectively analyzed, and knowledge, attitude, and practice (KAP) of66 Indian physicians were surveyed electronically.Results: A total of 60 (age 37.7 ± 18.4 years, 25 female) patients were included in the study (13 [21.7%] GP, 25 [41.7%] CIPO, 14 [23.3%]CI, and 8 [13.3%] overlap of GP and either CIPO [5] or CI [3]), of whom 40 had primary disorders and 20 had secondary disorders due todiabetes mellitus (n = 6), systemic sclerosis (n = 4), paraneoplastic (n = 2), infection (n = 3), Parkinson’s disease (n = 1), hypothyroidism(n = 1), hyperparathyroidism (n = 1), celiac disease (n = 1), and amyloidosis (n = 1). Primary disorders were more often misdiagnosed asfunctional GI disorders, causing diagnostic delays and complications, than secondary disorders. More patients in the primary disordergroup underwent surgery compared with those in the secondary group (25/40, 62.5% vs 1/20, 5%). A few rare infectious causes of GImotility disorders due to Strongyloides stercoralis, herpesvirus, and unidentified viruses were found. Of four patients treated with pyridostigminewith (n = 3) or without prucalopride (n = 1), three responded. Awareness about GI motility disorders, particularly the primarydisorders, among 66 doctors participating in the KAP survey was inadequate.Conclusion: Awareness regarding specific GI motility disorders among physicians is lacking, which leads to delay in diagnosis and resultsin more complications in patients, such as surgery, particularly in those with primary disorders.